Correction: Estimating NH3 and PM2.5 emissions from the Australia mega wildfires and the impact of plume transport on air quality in Australia and New Zealand. Issue 4 (20th June 2022) - Akdemir, Ece Ari; Battye, William H.; Myers, Casey Bray; Aneja, Viney P.
Abstract : Correction for 'Estimating NH3 and PM2.5 emissions from the Australia mega wildfires and the impact of plume transport on air quality in Australia and New Zealand' by Ece Ari Akdemir et al., Environ. Sci.: Atmos., 2022, ; https://doi.org/10.1039/d1ea00100k .